Satisfação conjugal e valores humanos dos casais de famílias intactas e recasadas - Almeida, Aline carvalho de (2016)
This master's dissertation aims to compare marital satisfaction and human values of couples from intact and remarried families. It sought further to develop and gather evidences of validity and accuracy of the Marital Satisfaction Scale (MSS) and know the valorative correlates of marital satisfaction and the predictive power of values with regard to this construct. In the Study 1, 208 married or in stable union couples (mage = 36; 58.7% female) participated, answering to marital satisfaction scale and sociodemographic questions. The principal components analysis suggested a tetra factorial structure that explained 50% of the total variance, whose specific factors had acceptable internal consistency (α = 0.91). In the Study 2, 214 married and remarried individuals (mage = 39; 53.3% female) participated, answering the Marital Satisfaction Scale (MSS), the Basic Values Questionnaire (BVQ) and sociodemographic questions. The results of confirmatory factorial analysis suggested that the Marital Satisfaction Scale showed adequate psychometric structure [χ² = 319.248; χ²/gl = 1.97; GFI = 0.87; AGFI = 0.83; CFI = 0.90; RMSEA = 0.068 (IC90% = 0.057 – 0.078); TLI = 0.88 e CAIC = 624.815]. The overall internal consistency index of the scale (20 items) was 0.89 and in each particular component: Affectivity (α = 0.80); Compatibility (α = 0.78); Incongruity (α = 0.79) and Financial Adjustment (α = 0.73). In the Study 3, by proceeding Pearson's correlation analysis it was noted that marital satisfaction was correlated significantly and positively with the subfunctions normative (r = 0.19; p < 0.01), suprapersonal (r = 0.20, p < 0.01) and interactive (r = 0.27; p < 0.01). When performing multiple linear regression (stepwise method) [R = 0.27, R² = 0.07; F (1.21) = 16.03; p < 0,001], it was noticed that only the interactive subfunction (β = 0.21; t = 4.00; p < 0,001) was able to predict marital satisfaction. Finally, it was performed multivariate analysis of variance (MANOVA). It was found that only the variable gender presented significant differences with regard to marital satisfaction [λ = 0.94, F (4.209) = 3.02, p < 0.05, size effect = 0.05], with men scoring higher than women. Regarding other sociodemographic variables (time of marriage, children, social class and religion) no significant differences were observed. Regarding the variability of human values based on the marital status (married or remarried), there was no significant difference. Regarding to the variability of marital satisfaction based on the marital status, it was found differences only in concern with the Affection factor [F (1; 2.197) = 4.92, p < 0.05, η = 0.02] in which people in first marriage scored higher than remarried. In conclusion, the objectives proposed in this dissertation were achieved, contributing to the understanding of relationships between human values and marital satisfaction as well as the variables involved in the promotion of harmony and happiness in marriage.